EVALUASI KINERJA ANGKUTAN UMUM DI KABUPATEN SIDOARJO - Supriyatno, Dadang; Widayanti, Ari (Jurnal Transportasi, 2015)
Abstract Public transportation is very important to support community activities in a city. The Lapindo mud disaster in Sidoarjo has impacts on community activities and public transportation travel patterns in the area. The performance of public transportation services in Sidoarjo is currently quite poor, with an average frequency of less than 6 vehicles/hour, an average headway of greater than 10 minutes, a load factor of less than 70 %, an average speed less than 30 km/hour, and an average travel time of less than 60 minutes. The low load factors could result in decreasing the revenue of public transportation operators which implies a decrease in welfare. In the field, around 20 % of public transportation vehicles are not operating in accordance with the route. In addition, some fleets are not in operation, especially on the route that led to the Porong area, because of the declining number of passengers as a result of the Lapindo mud disaster. For that reason, it is necessary for public transportation route network to adapt to impact map of the Lapindo mudflow and the development of the road network in Sidoarjo. Key words: public transportation, performance evaluation, load factor, headway, route Abstrak Angkutan umum sangat penting untuk mendukung aktivitas masyarakat di suatu kota. Bencana lumpur Lapindo di Sidoarjo berdampak pada aktivitas masyarakat dan pola perjalanan angkutan umum di daerah tersebut. Kinerja layanan angkutan umum di Kabupaten Sidoarjo saat ini kurang baik, dengan frekuensi rata-rata kurang dari 6 kendaraan/jam, waktu antara rata-rata lebih besar dari 10 menit, faktor muat kurang dari 70 %, kecepatan rata-rata kurang dari 30 km/jam, serta waktu tempuh perjalanan rata-rata kurang dari 60 menit. Faktor muat yang rendah berakibat menurunnya penghasilan operator angkutan umum yang berimplikasi pada penurunan kesejahteraan. Hal yang terjadi di lapangan adalah bahwa sekitar 20 % angkutan umum beroperasi tidak sesuai dengan ijin trayeknya. Selain itu beberapa armada tidak beroperasi, khususnya pada trayek yang menuju ke daerah Porong, karena menurunnya jumlah penumpang akibat bencana lumpur Lapindo. Untuk itu, diperlukan jaringan trayek angkutan umum yang disesuaikan dengan peta dampak lumpur Lapindo dan pengembangan jaringan jalan di Sidoarjo. Kata-kata kunci: angkutan umum, evaluasi kinerja, faktor muat, waktu antara, trayek